Experience as event: event cognition and the study of (religious) experiences - Taves, Ann (Religion, brain & behavior, 2017)
We argue that event is a basic concept that humanists, social scientists, and cognitive psychologists can use to build a consilient research platform for the study of experiences that people deem religious. Grounding the study of experience in event cognition allows us to reframe several classic problems in the study of "religious experience": (1) the function of culture-specific knowledge in the production of experiences; (2) the relationship between original experiences and later narratives; and (3) the role of appraisal processes in experience. At the same time, construing experiences as events allows us to integrate disparate lines of research in the cognitive science of religion (CSR) in a unified framework for studying both existing and emergent phenomena.